A multiple case study of the governing boards of two multilevel collaborations - Youngblood, Kerry, author; Davies, Timothy Gray, advisor; Harbour, Clifford P., committee member; Banning, James H., committee member; Hall, Bruce, committee member (Colorado State University. Libraries, 2006)
This study explores the perceptions, thoughts, and feelings of members of two organizations charged with the responsibility of leading their respective multilevel educational partnerships. In this situation, the cases are two multilevel partnerships, while the participants are the members of the two multilevel governing boards. The two cases are set in the Western United States, each one representing a local school district, a community college and a four-year institution of higher education. The method of study selected for this effort was a qualitative research design analyzed for emergent themes, using a multiple case study. In order to gain insight into this unique board culture of multilevel partnerships, the following research questions were asked: 1. What is the scope of feeling and perception of those who have experienced the challenges of merging disparate resources, differing cultures, and competing goals into a functional multi-level partnership? 2. How do board members view the various elements of structure that form the multilevel collaboration? The primary vehicle for acquiring the interview data was a series of unstructured open-ended interviews analyzed for emergent thoughts and themes. Two major themes emerged from the data: Collaboration and Community. Collaboration is a strong component of both cases and is consistent with the review of literature. Community is a robust theme that emerged from the data but does not emerge as a strong aspect of the literature. Participants displayed a strong commitment to community viewing population density as a significant factor in how they interact. In addition participants' reasons for participation were similar regardless of the scope of governing board responsibilities.
Keywords: school administration; educational administration